2013
DOI: 10.1002/jcc.23418
|View full text |Cite
|
Sign up to set email alerts
|

Computational protein design: The proteus software and selected applications

Abstract: We describe an automated procedure for protein design, implemented in a flexible software package, called Proteus. System setup and calculation of an energy matrix are done with the XPLOR modeling program and its sophisticated command language, supporting several force fields and solvent models. A second program provides algorithms to search sequence space. It allows a decomposition of the system into groups, which can be combined in different ways in the energy function, for both positive and negative design.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 46 publications
(98 citation statements)
references
References 119 publications
(192 reference statements)
0
98
0
Order By: Relevance
“…A similar conclusion was reached for a pair of Glu and Asp residues in the pocket P6 of DR and I-E molecules 44 . We used the empirical model Propka 45 and a constant-pH Monte Carlo approach implemented in the program PROTEUS 46 to compute the pK of titratable groups in the crystallographic structure of HLA-DQ8, both in the absence and the presence of the peptides insulin and VCL-DERAA. Both methods agreed that the residues aGLU31 and bGLU86, near pocket P1, are strongly correlated; the predicted pKa values suggested that one of them should be protonated, most probably aGlu31.…”
Section: Methodsmentioning
confidence: 99%
“…A similar conclusion was reached for a pair of Glu and Asp residues in the pocket P6 of DR and I-E molecules 44 . We used the empirical model Propka 45 and a constant-pH Monte Carlo approach implemented in the program PROTEUS 46 to compute the pK of titratable groups in the crystallographic structure of HLA-DQ8, both in the absence and the presence of the peptides insulin and VCL-DERAA. Both methods agreed that the residues aGLU31 and bGLU86, near pocket P1, are strongly correlated; the predicted pKa values suggested that one of them should be protonated, most probably aGlu31.…”
Section: Methodsmentioning
confidence: 99%
“…Future applications of many-body DEE may help determine whether the use of polarizable force fields (26) and self-consistent reactionfield implicit solvents (28)(29)(30) can overcome the limitations of previous generation pairwise force fields (14) and pairwise implicit solvents (21-23) for computational protein design (15)(16)(17).…”
Section: Structural Insights Into the Relative Stability Of Pcna Mutantsmentioning
confidence: 99%
“…The combination of low-energy side-chain rotamer libraries (8)(9)(10) with DEE (11,12) global optimization has been widely used for protein electrostatic network optimization and sequence design (13)(14)(15)(16)(17). However, rotamer elimination criteria have only been defined for pairwise-additive energy functions such as the OPLS-AA (18), AMBER (19), and CHARMM (20) families of fixed partial-charge force fields and pairwise decomposable continuum solvents (21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The secondary structure prediction resulted from the comparison of the following servers: HHpred, Quick2D [23], PredictProtein [24], Proteus 2.0 [25]. The transmembrane (TM) helices/region prediction was performed by interrogating the following servers: POLYVIEW-2D (117–138) [26], TMAP (115–132, 168–196, 370–398, 565–580) [27], TMPRED (8–25, 165–194) [28], Octopus (510–560) [29].…”
Section: Methodsmentioning
confidence: 99%